HMB-45 negative angiomyolipoma of the orbit: a case report and review of the literature. Issue 1 (December 2016) - Lin, Che-Yu; Tsai, Chieh-Chih; Kau, Hui-Chuan; Yu, Wei-Kuang; Kao, Shu-Ching; Liu, Catherine
Abstract Background Angiomyolipoma is a benign mesenchymal tumor composed of variable amounts of smooth muscle, adipose tissue and thick-walled blood vessels, and usually named PEComas (perivascular epithelioid cell tumors). PEComas share overlapping histopathological features with epithelioid cells along a perivascular distribution and characteristic immunohistochemistry with coexpression of myoid and melanocytic markers (HMB-45 /or Melan-A). We report the first case of primary orbital angiomyolipoma with negative melanocytic marker. Case presentation An 80-year-old Asian woman had a 2-year history of progressive swelling in the left upper eyelid. External examination revealed 3 cm of relative proptosis of the left eye and a palpable mass in the left superonasal orbit. Computed tomographic scan demonstrated a circumscribed, heterogeneous orbital mass. Excision biopsy was done and the histological finding demonstrated the orbital mass was composed of mature adipocytes, intermingled with spindle or oval-shaped cells, and accompanied by thick-walled blood vessels. Immunohistochemically, tumor cells were positive for CD34 and HHF-35, but negative for cytokeratin, HMB-45 and Melan-A. The diagnosis of angiomyolipoma was made. No recurrence was noted at 2-year follow-up. Conclusion In our case, the HMB-45 negativity may be explained by the rarity of the epithelioid cells, and the HMB-45 positivity is often weaker or absent in spindle cells. Angiomyolipoma, although rare, should be added to the differential diagnosis of space-occupying orbital lesion.